The future of global health after the Ebola outbreak - Camara, Mohamed Elmahady; Camara, Nafissatou (International Journal Of Community Medicine And Public Health, 2017)
Background: This article aims to address the future of Global Health after the Ebola outbreak in West Africa. It analyzes the effectiveness of the response provided from the beginning of the epidemic to its remission. Methods:The article is both retrospective and prospective. It is analytic. It is based on factual considerations rather than clinical trials. The article provides the last statistics provided by the World Health Organization. It discusses the rapid involvement of the scientific and the international community in the production of the vaccine against the Ebola virus. It briefly focuses on the cycle of the production of a vaccine which has not been respected in the case of the Ebola outbreak. Results: The Republic of Guinea recorded its first patients in March 2014. The authorities; at that beginning, remained slow in their response. That negligence resulted in hundreds of deaths in the community. The deadly virus killed thousands of people; mainly in Guinea, Sierra Leone and Liberia. Some of the countries that were previously affected by the virus are now declared free of Ebola, while Guinea continues to record some sporadic cases. Conclusions:It appears that the concept of global health was not working in the proper sense from 1976 to 2014. The concept started to work after noticing the rapid deaths of thousands of people in Guinea, Sierra-Leone, and Liberia. Also, the involvement of the United States of America has accelerated the process of the global response to the Ebola outbreak. Rapidly, a vaccine was developed with 100% effectiveness. The conclusion summarizes the future of Global Health in the World; mainly in Africa. The future of modern medicine will pass by the knowledge of the concept of Global Health which is an inclusive part of the Public Health. For example, Global Health is now taught in developed countries. After the Ebola outbreak, universities in Africa and around the world must include the teaching of Global Health in their curriculum.